How digital photography works - White, Ron, 1944- (How it works., 2005)
Remember when digital cameras first came on the market a few years ago? Like most people, you probably waited to buy one, waiting to see if it was just a fad or if it was going to become a way of life, much like PCs did in the 1980s. Well, years have gone by and digital cameras are only getting better with time. Yet it seems like more people have digital cameras than know how to use them. How Digital Photography Works is a digital camera and photography book that actually tells you how it all works. Full-color, large illustrations take the guesswork out of understanding all of the cool things your digital camera and software can do, from capturing images to fixing mistakes. You will learn: How a lens works How exposure works How digital cameras transform light to become data How digital cameras manipulate photos How digital tools correct picture-taking mistakes How digital print-making works So much more How Digital Photography Works is the only book that gives you a behind the scenes look at digital photography, ultimately making you a better digital photographer.